If In Doubt, Sit Them Out? - Exploring the Influence of the ‘Recognise and Remove’ Process on Management Decisions and Player Disclosure in Community Rugby Union - Badenhorst, Marelise; Salmon, Danielle; Rasmussen, Karen; Sole, Gisela; Walters, Simon; Romanchuk, Janelle (Elsevier BV, 2026)
Objectives: World Rugby's ‘Recognise and Remove’ process facilitates immediate removal of players with suspected concussion from community-level games to enhance player safety. The aim of this study was to explore community stakeholders' perceptions of the ‘Recognise and Remove’ process, and its influence on concussion management decisions. Design: Pragmatic, qualitative descriptive study. Methods: This study utilised semi-structured interviews and focus groups with 62 community rugby stakeholders from New Zealand schools and clubs. Reflexive thematic analysis was used to analyse the data. Results: Four main themes were developed: i) If in doubt, sit them out; ii) hypervigilance and a pendulum that has swung too far; iii) decisions have consequences: the influence of uncertainty and pressure; and iv) the mandatory stand-down period can be counter-productive. Most participants emphasised the importance of the process, placing player welfare above all else. However, several participants believed that improved concussion awareness had created hypervigilance which in their opinion is detrimental to the game. Immediate decision-making to remove a player was becoming increasingly challenging under pressure. Finally, the mandatory stand-down period was a primary driver for player non-disclosure, and feelings of stress experienced by team leads/physiotherapists when uncertainty surrounded the suspected concussion. Conclusions: Most participants emphasised the importance of the ‘Recognise and Remove’ process. Yet, a concerning subset of participants expressed dissatisfaction with the process, leading to hesitancy when deciding to remove a player from the field. Collaborative strategies to improve stakeholders' acceptance of the process are critical to avoid unintended consequences.
Keywords: Concussion management; Qualitative research; Rugby union; 4203 Health Services and Systems; 42 Health Sciences; 1106 Human Movement and Sports Sciences; 1116 Medical Physiology; 1117 Public Health and Health Services; Sport Sciences; 3202 Clinical sciences; 4207 Sports science and exercise; 5201 Applied and developmental psychology